High Rates of Severe Hypoglycemia among African American Patients with Diabetes: The Surveillance, Prevention, and Management of Diabetes Mellitus (SUPREME-DM) Network - Karter, Andrew J (J Diabetes Complications, 2017)
AIMS: Seven-year surveillance study (2005–2011) to evaluate race/ethnic differences in the trends in rates of severe hypoglycemia (SH) in a population of insured, at-risk adults with diabetes. METHODS: SH events were identified via any primary or principal diagnosis from emergency department or inpatient encounters among African American, Asian, Latino and White adult diabetes patients treated with insulin or secretagogues (Sulfonylureas or Meglitinides), receiving care from integrated healthcare delivery systems across the United States. We calculated age- and sex-standardized annual SH rates and average annual percent change (AAPC) in SH rates. RESULTS: Annual SH rates ranged from 1.8% to 2.1% during this 7-year observation period (2,200,471 person-years). African Americans had consistently higher SH rates compared with Whites, while Latinos and Asians had consistently lower rates compared with Whites in each of the 7 years (all p<0.01). The trend increased significantly only among African Americans (AAPC = +4.3%; 95% CI: +2.1, +6.5%); in the other groups, the AAPC was not significantly different from zero. CONCLUSIONS: Surveillance efforts should monitor the racial/ethnic-specific rates. The factors underlying substantially higher rates of hypoglycemia in African Americans should be evaluated. Clinically and culturally-appropriate strategies to reduce the risk of SH need to be developed and tested.